2004
DOI: 10.1002/ca.20014
|View full text |Cite
|
Sign up to set email alerts
|

Linear parameters of normal and abnormal cava septi pellucidi: A post‐mortem study

Abstract: Anatomical variations in the dimensions of different brain structures have been correlated with clinical syndromes. This study on the parameters of normal and abnormal cavum septi pellucidi (CSP) can be of clinical significance. We obtained 479 brains from autopsied persons (310 males and 169 females, 377 normal or asymptomatic and 102 abnormal or symptomatic persons, aged 22-89 years) and observed that 110 brains (75 males and 35 females) had CSP. These cava were classified into two groups depending on the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 32 publications
0
8
2
3
Order By: Relevance
“…Although CT scans revealed that the prevalence of CSP ranged from 0.15% to 28% in adult patients, the studies using MRI scans reported higher rates that ranged from 5.1% to 58.7%. The prevalence of CSP in cadavers was found to be 22.96% in all cases, while the prevalence rate was 10.61% in the asymptomatic group [1]. In the present study, MRI scans revealed that the prevalence of CSP was found to be 3.7%, which is lower than the reported prevalence rates.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Although CT scans revealed that the prevalence of CSP ranged from 0.15% to 28% in adult patients, the studies using MRI scans reported higher rates that ranged from 5.1% to 58.7%. The prevalence of CSP in cadavers was found to be 22.96% in all cases, while the prevalence rate was 10.61% in the asymptomatic group [1]. In the present study, MRI scans revealed that the prevalence of CSP was found to be 3.7%, which is lower than the reported prevalence rates.…”
Section: Discussioncontrasting
confidence: 84%
“…The overall prevalence rate was 22.96%. In addition, CSP dimensions were significantly longer and wider in the symptomatic group [1]. In the present study, the prevalence of CSP on MRI scans was 3.7%, a rate lower than that in the asymptomatic group.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…A definição de um CSP alargado não é consensual na literatura, mas muitos trabalhos têm utilizado 6 mm como ponto de corte para tentar separar os CSPs variantes da normalidade daqueles que possam carregar algum significado patológico 5,6,18,21,22,24,25,26,27 . Além das dimensões lineares, a classificação subjetiva 28,29,30 em graus também parece ser útil na diferenciação entre CSP patológico e variante anatômica.…”
Section: Csp Como Variante Da Normalidadeunclassified